Enterpreneur Dalam Pendidikan Islam Inovasi dan Kreativitas Produk Usaha di Sekolah: Perspektif Pendidikan Islam - Randi Saputra Amyus; Agustiar; Nini Aryani (GHIROH, 2025)
This study aims to analyze the application of innovation and creativity in developing business products within the school environment from the perspective of Islamic Education. Using a qualitative descriptive approach, the research examines how Islamic values such as honesty, trustworthiness (amanah), and justice can be integrated into the entrepreneurial process in schools and their impact on students’ character and skills. Data were collected through direct observation, in-depth interviews with teachers and students, and document analysis of entrepreneurship programs implemented in several schools. The results show that applying Islamic principles in entrepreneurial activities not only enhances the quality of students’ business products but also plays a crucial role in shaping students’ integrity and responsibility. Moreover, students’ creativity and innovation in developing products that benefit the community significantly improved. These findings emphasize that integrating Islamic education and entrepreneurship within the school context not only boosts intellectual abilities but also cultivates a generation of young people with strong character, ethical values, and high competitiveness to face future challenges.